Identification of Directed Interactions in Kinematic Data during Running - Nakashima, Giovana Y.; Nakagawa, Theresa H.; dos Santos, Ana F.; Serrão, Fábio V.; Bessani, Michel; Maciel, Carlos D. (Frontiers in Bioengineering and Biotechnology, 2017)
The knowledge of motion dynamics during running activity is crucial to enhance the development of rehabilitation techniques and injury prevention programs. Recent studies investigated the interaction between joints, using several analysis techniques, as cross-correlation, sensitivity analysis, among others. However, the direction of the joints pairing is still not understood. This paper proposes a study of the influence direction pattern in healthy runners by using kinematic data together with partial directed coherence, a frequency approach of Granger causality. The analysis was divided into three anatomical planes, sagittal, frontal and transverse, and using data from ankle, knee, hip and trunk segments. Results indicate a predominance of proximal to distal influence during running, reflecting a centralized anatomic source of movements. These findings highlight the necessity of managing proximal joints movements, in addition to motor control and core (trunk and hip) strengthening training to lumbar spine, knee and ankle injuries prevention and rehabilitation.